Nutrition Education for Overweight Children Through Interactive Learning Media - Ngurah Mahendra Dinata; Dek Ngurah Laba Laksana; Dimas Qondias (Jurnal Edutech Undiksha, 2024)
Nutrition education interactive multimedia can be an alternative medium to deliver nutrition education material to overweight children. An interactive multimedia tool can provide information interactively by combining text, images, animation, audio, and video. This study aimed to develop interactive multimedia nutrition education that is valid and practical for overcoming the problem of overweight students in junior high schools. This research is research and development using the ADDIE media development model, which consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The data collection instruments used were validity test sheets and questionnaires. The data were then analyzed qualitatively and quantitatively. The data analysis found that the developed interactive multimedia proved valid and practical, with a validity level of 3.50 with a feasible category for use and a practicality level of 3.76 with good criteria. Based on the results of the study, it can be concluded that interactive multimedia nutrition education is useful and practical use in the delivery of nutrition educational material for schoolchildren who are experiencing overweight problems so that multimedia can be used at school as a means of nutritional education while reducing the number of students suffering from overweight and obsessions.